2012
DOI: 10.1136/archdischild.2011.301180
|View full text |Cite
|
Sign up to set email alerts
|

A disjointed effort: paediatric musculoskeletal examination

Abstract: MSK examination is not performed routinely during paediatric admissions in contrast to the examination of other symptoms regardless of the presenting complaint. This may need to be addressed by local audit and increased undergraduate teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Several authors have cited a lack of confidence in musculoskeletal diagnostic skills amongst primary care physicians as a reason for the high rate of unnecessary referrals [21][22][23][24][25][26][27][28], and have called for improved musculoskeletal education as part of entry-level medical education. The American Academy of Paediatrics in 2002 published guidelines for primary care physicians on referral for specialist opinion [29], but subsequent studies found that this publication has had no effect on referral patterns [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have cited a lack of confidence in musculoskeletal diagnostic skills amongst primary care physicians as a reason for the high rate of unnecessary referrals [21][22][23][24][25][26][27][28], and have called for improved musculoskeletal education as part of entry-level medical education. The American Academy of Paediatrics in 2002 published guidelines for primary care physicians on referral for specialist opinion [29], but subsequent studies found that this publication has had no effect on referral patterns [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequency of these complaints, a significant number of pediatricians are not confident in their skills to examine the musculoskeletal system properly [6], and musculoskeletal examination is not routinely performed during pediatric admissions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Initial suspicion in these cases was traumatic origin (painful pronation predominantly). As we mentioned before, there is a lack of awareness in relation to musculoskeletal examination in formative programs in pediatrics, 5 that could explain this phenomenon. On the other hand, we would like to emphasize how important a correct anamnesis is to know the causal mechanism of the traumatic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lack of knowledge about musculoeskeletical physical examination might also be a contributing factor. 5 Delay in starting treatment could increase the risk of complications and sequels.…”
mentioning
confidence: 99%
See 1 more Smart Citation